If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -2) + 3x = -6 Reorder the terms: -3(-2 + x) + 3x = -6 (-2 * -3 + x * -3) + 3x = -6 (6 + -3x) + 3x = -6 Combine like terms: -3x + 3x = 0 6 + 0 = -6 6 = -6 Solving 6 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 1000000009+3009000= | | 2x-20-64=0 | | 4(2-3b)=62 | | 9u+4=19 | | y^2-y-132=0 | | g(x)=log(x-5) | | 8R-2=2R+6-4R | | 8x-(2x+6)=24 | | 9x^2+18y^4= | | 66*8= | | 32b^2+12b= | | 3u+(u-2)=10 | | y^2-10y=-23 | | (x-2)5=0 | | (x-2)5=x | | 6a^3+15a= | | 5x+3y=-8 | | 5r^2-26r=24 | | 4b^2-17b=15 | | 18.3x-7.6=8.4x-14.6 | | 3t^2-13t-16=0 | | (2x+1)(x-4)(3x+5)=0 | | 5x-2(x-2)=11 | | -8x+20+10x=42 | | 3x-7=9+7x | | x+8=-2-x | | 15x^2+2xy-8y^2=0 | | 80x=-280 | | 100x=400 | | 2(x+2)=3(3x-4) | | 23x+10=28x+30 | | 21x+2=21x+11 |